SIMULASI DAMPAK PERUBAHAN IKLIM TERHADAP KETERSEDIAAN AIR TANAMAN TEBU DI WILAYAH MALANG - Firmanda Rizky Haditiya; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2018)
This study was held based on climate change impact as a present and future environmental issues on sustainable agriculture especially it’s impact on crop water availability. This study aimed to determine the impact of climate change on the water availability of sugarcane that was simulated using climate change scenarios based on global climatic analysis. Climate change was simulated for future scenarios using combination of temperature increase (2o, 4o, and 6o C) and rainfall change (∆CH -10, ∆CH -5, ∆CH +5, ∆CH +10%) from actual condition. This study took place at Wajak, Sumbermanjing, and Gedangan sub-districts, choosen by sugarcane plantation area with different soil conditions, especially soil texture. The result showed water demand increased 5-15% with the increasing of temperature, thus could impacting crop water availability especially during dry months period which could not fulfill crop water needs. The highest potential reduction was in Gedangan site which reached 5,1% in the C9 scenario (temperature + 6o C and rainfall -10%). The high quality in holding water could not assure the low potential reduction because it also depends on climatic conditions.